A Semiotic Analysis of Meaning in Selected Poems by Langston Hughes Based on Peirce’s Theory of Signs - Insyari Mokoginta; Mery Balango; Adriansyah A. Katili (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This study examines the implied meanings in three selected poems by Langston Hughes—“I, Too,” “The Weary Blues,” and “Harlem”—using Charles Sanders Peirce’s theory of signs. The study aims to identify how icons, indices, and symbols function in constructing meaning within the poems. A descriptive qualitative method with document analysis is employed to examine textual elements and semiotic relations. The findings reveal that I, Too predominantly utilizes indexical and symbolic signs to express racial exclusion, identity, and the demand for social recognition. The Weary Blues demonstrates the most complex semiotic structure, as it incorporates icons, indices, and symbols to convey musical expression, emotional suffering, and cultural resilience. In contrast, Harlem relies mainly on symbolic signs to represent the psychological tension and social implications of a deferred dream. Overall, this study confirms that Peirce’s semiotic framework effectively uncovers the implied meanings in Hughes’s poetry and illustrates how semiotic signs serve as a medium for articulating African American experiences and social criticism.